Indicadores de depressão materna e sintomas psicofuncionais em bebês: uma compreensão psicanalítica - Silva, Heloisa Cardoso da (Universidade do Vale do Rio dos Sinos, 2014)
This dissertation deals with psychofunctional symptoms in babies of mothers with depression indicators, and has psychoanalysis as theoretical framework. Thus, it’s composed of two articles, a theoretical and an empirical. In the theoretical article, entitled "Depression and Motherhood Based on Psychoanalysis: A Systematic Review of the Literature", a survey of national scientific production on depression and motherhood was carried out, with psychoanalytic framework, in the period from January 2003 to January 2014. The results showed the shortage of studies on maternal depression and early symptoms in babies, justifying the research presented in the empirical article. In empirical article, entitled "Psychofunctional Symptoms and Maternal Depression: A Qualitative Study", it was performed a study of multiple cases, with the objective of comprehending the manifestation of psychofunctional symptoms in infants between six and 12 months, whose mothers present maternal depression indicators. Participated in this study three mother-infant pairs, and the finding showed that, in this context, mothers encounter difficulties in the exercise of motherhood and the tasks that it requires, leading babies to defend themselves precociously, expressing their suffering through the symptoms. Therefore, it's hoped that this work will contribute to the understanding and scientific development in the studied area, fostering further researches and subsidizing the construction of preventive and health-promoting strategies together with mothers and babies.
Keywords: Depressão materna; Sintoma psicofuncional; Maternidade; Relação mãe-bebê; Maternal depression; Psychofunctional symptom; Motherhood; Mother child relations; ACCNPQ::Ciências Humanas::Psicologia